Gestational diabetes mellitus placentas exhibit epimutations at placental development genes. Issue 13 (9th December 2022) - Meyrueix, Laetitia P.; Gharaibeh, Raad; Xue, Jing; Brouwer, Cory; Jones, Corbin; Adair, Linda; Norris, Shane A.; Ideraabdullah, Folami
ABSTRACT: Gestational diabetes mellitus (GDM) is a maternal metabolic disorder that perturbs placental development and increases the risk of offspring short- and long-term metabolic disorders. The mechanisms by which GDM impairs placental development remain poorly understood. Here, we defined the DNA methylome of GDM placentas and determined whether GDM perturbs methylation at genes important for placental development. We conducted an epigenome-wide association study of 42 placentas from pregnancies in the South African Soweto First 1000 days cohort (S1000). Using genome-wide bisulfite sequencing, we compared non-GDM placentas to GDM placentas with similar proportions from obese and non-obese mothers. Compared to non-GDM, GDM placentas exhibited a distinct methylation profile consisting of 12, 210 differentially methylated CpGs (DMCs) that mapped to 3, 875 genes. Epigenetically altered genes were enriched in Wnt and cadherin signalling pathways, both critical in placentation and embryogenesis. We also defined regional DNA methylation perturbation in GDM placentas at 11 placental development genes. These findings reveal extensive changes to the placental epigenome of GDM pregnancies and highlight perturbation enriched at important placental development genes. These molecular changes represent potential mechanisms for GDM-induced placental effects that may serve as candidate biomarkers for placental, maternal, and foetal health. Using a study design that used similar proportions of obese and non-obese mothers in our case and control pregnancies, we minimized the detection of changes due to obesity alone. Further work will be necessary to investigate the extent of the influence of obesity on these GDM-related placental epigenetic changes.